Up against a wall : rape reform and the failure of success - Corrigan, Rose (New York : New York University Press, 2016)
This volume discusses how and why legal and medical institutions continue to resist implementing reforms intended to provide more just and compassionate responses to victims of sexual violence.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Rape -- United States; Rape victims -- Legal status, laws, etc. -- United States; Law reform -- United States; Anti-rape movement -- United States; Feminist theory -- United States; Law; United States of America, USA; Violence in society; Feminism & feminist theory; Law & society, gender issues; Criminal law: procedure & offences